Prochlorococcus as a Possible Source for Transparent Exopolymer Particles (TEP) - Iuculano, Francesca; Mazuecos, Ignacio P.; Reche, Isabel; Agustí, Susana (Frontiers in Microbiology, 2017)
Transparent exopolymer particles (TEP), usually associated with phytoplankton blooms, promote the formation of marine aggregates. Their exportation to deep waters is considered a key component of the biological carbon pump. Here, we explored the role of solar radiation and picocyanobacteria in the formation of TEP in oligotrophic surface waters of the Atlantic and Pacific Oceans in ten on-deck incubation experiments during the Malaspina 2010 Expedition. TEP concentrations were low on the ocean’s surface although these concentrations were significantly higher on the surface of the Pacific (24.45 ± 2.3 µg XG Eq L-1) than on the surface of the Atlantic Ocean (8.18 ± 4.56 µg XG Eq L-1). Solar radiation induced a significant production of TEP in the on-deck experiments from the surface water of the Pacific Ocean, reaching values up to 187.3 µg XG Eq L-1 compared with the low production observed in the dark controls. By contrast, TEP production in the Atlantic Ocean experiments was lower, and its formation was not related to the light treatments. Prochlorococcus sp. from the surface ocean was very sensitive to solar radiation and experienced a high cell decay in the Pacific Ocean experiments. TEP production in the on-deck incubation experiments was closely related to the observed cell decay rates of Prochlorococcus sp., suggesting that this picocyanobacteria genus is a potential source of TEP. The evidence to propose such potential role was derived experimentally, using natural communities including the presence of several species and a variety of processes. Laboratory experiments with cultures of a non-axenic strain of Prochlorococcus marinus were then used to test TEP production by this genus. TEP concentrations in the culture increased with increasing cell abundance during the exponential phase, reaching the highest TEP concentration at the beginning of the stationary phase. The average TEP concentration of 1474 ± 226 µg XG Eq L-1 (mean±SE) observed at the stationary phase of P. marinus cultures is comparable with the values reported in the literature for diatom cultures, also growing in non-axenic as well as axenic cultures. Our results identify Prochlorococcus sp. as a possible relevant source of TEP in the oligotrophic ocean.